Role of PSA in Diagnosing Carcinoma Prostate in India: Is the Situation Same as in Developed Countries - Dhangar, Dr. Sanjay P. (SP'z Series New Insights on Urology and Urological Research Part I, 2022)
Background: Prostate cancer has become the single most common non-cutaneous malignancy in men. Its incidence has been rising rapidly in most countries including low risk countries like India. Present study deals with the PSA value in patients with prostatic symptoms and its correlation with the prostatic biopsy specimen. Purpose: i) Co-relation of raised PSA in non- carcinoma prostate patients. ii) At what stage does carcinoma of prostate gets diagnosed in Indian scenario. iii) What are the treatment options opted by the patients who are diagnosed with carcinoma of prostate for the first time. Materials and Methods: First 500 patients that presented with lower urinary tract symptoms and prostatic enlargement through the casualty department, outpatient department and in patient department of the Department of Urology, Ruby Hall Clinic, Pune from March 2012 to February 2014 were included in the present study. Prostatic biopsy was done in cases with either increased serum PSA level and/or palpable nodule and/or suspicious TRUS findings or a combination of two out of these 3 factors. Results: Mean PSA value is 8.5ng/ml in BPH patients, indicating higher values in Indian patients, due to prostatitis. Maximum carcinoma prostate patients presented late with metastases. As the limit of PSA value for diagnosis of carcinoma prostate increases from 4ng/ml to 15ng/ml the sensitivity decreases and the specificity and diagnostic accuracy increases. The patients of carcinoma prostate received treatment as per their stage of presentation. Conclusion: In Indian context there is an overall baseline elevation of lower minimum level of the normal PSA. This is probably due to association of prostatitis in Indian population.